Introduction: unthinking language from a posthumanist perspective - Schneider, Britta; Heyd, Theresa (Signs and society, 2024)
In this special issue, we inspect material and nonhuman phenomena that contribute to interaction and meaning-making—among them sounds, visual signs, animals, images, digital devices, bodies, and movements—in order to stimulate new thinking surrounding the question of what language is from a posthumanist perspective. The contributors are language-oriented scholars who focus on material and technological environments in language. They interrogate how linguistic and nonlinguistic practices interrelate to produce meaning, concepts of the human, and social relations. The theoretical backgrounds of such posthumanist approaches to the sociomaterial practice of interaction are introduced in this article.
Gesehen am 02.07.2024